Micro-costing analysis of guideline-based treatment by direct-acting agents: the real-life case of hepatitis C management in Brazil. Issue 1 (December 2017) - Perazzo, Hugo; Jorge, Marcelino; Silva, Julio; Avellar, Alexandre; Silva, Patrícia; Romero, Carmen; Veloso, Valdilea; Mujica-Mota, Ruben; Anderson, Rob; Hyde, Chris; Castro, Rodolfo
Abstract Background Eradication of hepatitis C virus (HCV) using direct-acting agents (DAA) has been associated with a financial burden to health authorities worldwide. We aimed to evaluate the guideline-based treatment costs by DAAs from the perspective of the Brazilian Ministry of Health (BMoH). Methods The activity based costing method was used to estimate the cost for monitoring/treatment of genotype-1 (GT1) HCV patients by the following strategies: peg-interferon (PEG-IFN)/ribavirin (RBV) for 48 weeks, PEG-IFN/RBV plus boceprevir (BOC) or telaprevir (TEL) for 48 weeks, and sofosbuvir (SOF) plus daclastavir (DCV) or simeprevir (SIM) for 12 weeks. Costs were reported in United States Dollars without (US) and with adjustment for purchasing power parity (PPP). Drug costs were collected at the National Database of Health Prices and an overview of the literature was performed to assess effectiveness of SOF/DCV and SOF/SIM regimens in real-world cohorts. Results Treatment costs of GT1-HCV patients were PPP 43, 176.28 (US 24, 020.16) for PEG-IFN/RBV, PPP 71, 196.03 (US 39, 578.23) for PEG-IFN/RBV/BOC and PPP 86, 250.33 (US 47, 946.92) for PEG-IFN/RBV/TEL. Treatment by all-oral interferon-free regimens were the less expensive approach: PPP 19, 761.72 (US 10, 985.90) for SOF/DCV and PPP 21, 590.91 (US 12, 002.75) for SOF/SIM. The overview reported HCV eradication in up to 98% for SOF/DCV and 96% for SOF/SIM. Conclusion Strategies with all oral interferon-free might lead to lower costs for management of GT1-HCV patients compared to IFN-based regimens in Brazil. This occurred mainly because of high discounts over international DAA prices due to negotiation between BMoH and pharmaceutical industries.